Quality and reporting of patient-reported outcomes in elderly patients with hip fracture: a systematic review - R Marijn Houwert; Marilyn Heng; Sandra Wilson; Puck van der Vet; Egbert-Jan Verleisdonk (BMJ Open)
Objective To assess how patient-reported outcomes (PROs) are reported and to assess the quality of reporting PROs for elderly patients with a hip fracture in both randomised controlled trials (RCTs) and observational studies.Design Systematic review.Data sources Medline, Embase and CENTRAL were searched on 1 March 2013 to 25 May 2021.Eligibility criteria RCTs and observational studies on geriatric (≥65 years of age) patients, with one or more PRO as outcome were included.Data extraction and synthesis Primary outcome was type of PRO; secondary outcome and quality assessment was measured by adherence to the Consolidated Standards of Reporting Trials (CONSORT) extension for patient-reported outcomes (CONSORT-PRO). Because of heterogeneity in study population and outcomes, data pooling was not possible.Results 3659 studies were found in the initial search. Of those, 67 were included in the final analysis. 83.6% of studies did not adequately mention missing data, 52.3% did not correctly report how PROs were collected and 61.2% did not report adequate effect size. PRO limitations were adequately reported in 20.9% of studies and interpretation of PROs was adequately reported in 19.4% of studies. Most Quality of Life (QoL) outcomes were measured by the EuroQol 5-Dimension 3-Levels, and pain as well as patient satisfaction by Visual Analogue Scale.Conclusion This study found that a high variety of PRO measures are used to evaluate geriatric hip fracture care. In addition, 47.8% of studies examining PROs in elderly patients with hip fracture do not satisfy at least 50% of the CONSORT-PRO criteria. This enables poorly conducted research to be published and used in evidence-based medicine and, consequently, shared decision-making. More efforts should be undertaken to improve adequate reporting. We believe extending the CONSORT-PRO extension to Strengthening the Reporting of Observational Studies in Epidemiology for observational studies would be a valuable addition to current guidelines.